Cybercrime and its victims - Martellozzo, Elena; Jane, Emma A. 19XX- (Routledge studies in crime and society, 2017)
Foreword / Majid Yar -- Introduction : victims of cybercrime on the small "i" internet / Elena Martellozzo and Emma A. Jane, Part I: Conceptual issues -- Victims of cybercrime : definitions and challenges / Nicole A. Vincent -- Theorising power online / Chris Brickell -- Sexual violence, abuse, and exploitation -- Gendered cyberhate, victim-blaming, and why the internet is more like driving a car on a road than being naked in the snow / Emma A. Jane -- Sexting in context : understanding gendered sexual media practices beyond inherent "risk" and "harm" / Amy Shields Dobson -- Victims of sex trafficking and online sexual exploitation / Kristine Hickle -- Online sexual grooming : children as victims of online abuse / Elena Martellozzo -- Race and culture -- Online racial hate speech / Jamie Cleland -- Malign images, malevolent networks : social media, extremist violence and public anxieties / Ramaswami Harindranath -- Social violence -- Bullying in the digital age / Robin M. Kowalski and Gary W. Giumetti -- Internet suicide and communities of affirmation / Ronald Niezen -- Conclusions -- Conclusion beyond law : protecting victims through engineering and design / Nicole A Vincent and Emma A. Jane